Analisis Nilai Kontribusi Bantuan Kemanusiaan Palestina Badan Amil Zakat Nasional (BAZNAS) Tahun 2018-2021 - Muhammad Abdi Ridha; Ibdalsyah; Qurroh Ayuniyyah (Department of Islamic Economics, IPB University, 2022)
Since the Jews declared the establishment of the state of Israel in the Palestinian territories in 1948, Indonesia has been part of the party opposing the Israeli occupation and supporting the Palestinian people's efforts to gain their right to independence. In terms of humanitarian assistance, zakat, infaq and alms management institutions are increasingly promoting various humanitarian aids, one of which is the Indonesia’s National Zakat Agency (BAZNAS). This study aims to analyze the value of the contribution of zakat, infaq and alms funds by BAZNAS for humanitarian aid in Palestine. The sampling method used in this research is purposive sampling. Data is described using descriptive analysis. The results of this study indicate that the value of the contribution to the distribution of ZIS funds for Palestinian humanitarian assistance carried out by BAZNAS in 2018-2021 is volatile. The largest distribution of zakat funds for Palestinian humanitarian aid occurred in 2018 which was 2,531,430,175.00. While the largest infaq and alms funds occurred in 2021, which amounted to 597,268,865.00. The factor that causes this fluctuation in the level of distribution is because the value of distributing Palestinian humanitarian aid depends on the pattern of cooperation built by BAZNAS with other humanitarian institutions.